Quality of Life and Healthcare Seeking Behavior among Internal Migrant Laborers in Coimbatore, India: A Community-based Analytical Cross-sectional Study - P Aparnavi; M Malarkodi; Sivagami Ramanathan; Madhavi Sambandan; Jeevithan Shanmugam; Mohan Kumar; Shanmuga Priya; Seetharaman Narayanan; Ramesh Rathinamoorthy (Indian Journal of Community Medicine)
Background: Globalization and urbanization have increased international and internal migration. However, migrants are still not absorbed into the local communities and remain vulnerable groups. Hence, the present study aimed to determine the quality of life (QoL) and healthcare-seeking behavior (HCSB) of internal migrant laborers in Coimbatore, Tamil Nadu. Methodology: An analytical cross-sectional study was conducted in the year 2023 among 321 migrant laborers residing for a minimum duration of 6 months in Coimbatore. A pre-tested questionnaire was used to collect data on socio-demography, QoL (using the WHO BREF scale), HCSB, and healthcare expenses. Ethical clearance was obtained from the institutional ethical committee. Informed written consent was obtained from the participants. Data were analyzed using SPSS version 27. Mann–Whitney U test and Kruskal–Wallis test were used to compare QoL across socio-demographics and HCSB. Results: The overall QoL score was 61, and those in social and environmental domains were also above 60. The QoL was higher in the environmental and social domains than in the physical and psychological domains. Females, married people, those currently living with their family, those working in the organized sector, and those in higher socio-economic status had better QoL than their counterparts. Per capita income had a positive correlation with physical, psychological, and environmental aspects of life. About 68% of those who used private sector healthcare services had catastrophic health expenditures (CHEs). Conclusion: The overall QoL among migrant laborers was moderate. Migrants preferring formal healthcare enjoyed better QoL. Major CHE was for delivery, and hence, the barriers to accessing free government services are to be explored.